(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
This study aims to analyze the effect of applying inquiry learning strategies to the lack of critical thinking and creativity in elementary school students. The method used is a qualitative method based on the results of literatureresearch, namely collecting data from books, journals, theses, and others related to the relationship in the discussion. Elementary Student Creativity. In its implementation, this inquiry approach trains students on problems that have intellectual challenges and is planned in activities whose purpose is to guide children to be able to find something for themselves.